Comics and studies on brain functions - Micaela Morelli (Between, 2018)
The important role of Comics, in communication related to popular contexts and with people of all ages is undoubted. The meaning of comics goes beyond the pure representation of an image with a text, and this is one of the reasons why Comics have been used, in some instances, to study brain functions related to emotions, humourappreciation, image comprehension and visual language. In the past 20 years, the availability of instruments that could measure the activity of the brain in vivohas allowed us to develop experimental paradigms aimed at exploring the neural changes related not only to simple behaviours but also to increasingly complex functions such as emotions and consciousness [...]